Analysis of Students’ Difficulties in Speaking Arabic in the Kalam Course - Rantisi, Muhamad Zia; Rosdiana, Siti; Saputra, Aditia; Fauzan, Achmad; Lukman, Lukman; Fadliansyah, Azhimy (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeru Sultan Aji Muhammad Idris Samarinda, 2022)
Arabic speaking skill (maharah al-kalam) is one of the essential competencies in Arabic language learning at the university level. However, many students still experience various difficulties in using Arabic actively and communicatively. This study was conducted due to the low level of students’ speaking proficiency, which may affect the effectiveness of Arabic language learning as well as students’ academic readiness to comprehend and use Arabic in higher education settings. The study aims to analyze students’ difficulties in speaking Arabic in the Kalam course and to identify the factors influencing these difficulties. This research employed a descriptive qualitative approach. Data were collected through observations, semi-structured interviews, and documentation involving students and the lecturer of the Kalam course. The data were analyzed using the interactive model proposed by Miles, Huberman, and Saldaña, which consists of data reduction, data display, and conclusion drawing. The findings revealed that students’ difficulties were influenced by both linguistic and non-linguistic factors. Linguistic factors included limited vocabulary mastery, difficulties in applying nahwu and sharaf rules, weak pronunciation of Arabic letters, and low spontaneous speaking ability. Meanwhile, non-linguistic factors comprised low self-confidence, speaking anxiety, lack of practice, limited language environment, and teaching methods that were not fully communicative. This study contributes to the development of maharah al-kalam learning through more communicative approaches and the establishment of a supportive language environment. Future studies are recommended to develop technology-based Arabic speaking learning models integrated with bi’ah lughawiyah.